Infrastructure finance in Europe insights into the history of water, transport, and telecommunications - Cassis, Youssef; De Luca, Giuseppe; Florio, Massimo (Oxford University Press, 2016)
The social returns of investment in water, roads and railways are apparent in the long run, but this distant horizon poses problems to governments and investors. This volume explores the different historical paths to solving the problem of infrastructure finance in Europe, from the fall of the Roman Empire to the end of the 20th century.